Spanish Migration towards America from the Perspective of the Emigrant´s Handbook [Cartilla del Emigrante] (1910) - Pérez Acevedo, Martín (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The publication of the Emigrant´s Handbook [ Cartilla del Emigrante] in 1910, by the Ibero-American Union responded to the effort of directing and informing Spanish citizens who wished to migrate to America, in order to improve their life conditions. In this work, its authors Jesús María Rísquez, medical doctor, and Melchor Ordoñez, teacher, explained the particularities represented by both the legal and illegal transfer.In this way, knowledge of the migratory framework on both sides of the Atlantic was pondered; which in theory guaranteed full exercise of rights and obligations. In the opinion of Rísquez and Ordoñez, it was fundamental to warn about the shipping lines and travel conditions, especially with regards to trip payment and the sanitary medical scenery of the journey. The potentialities and physical characteristics of destination countries in the American continent were equally pointed out, as well as the work profile of the Spanish migrant, which would allow easier insertion. For this reason, fulfillment of the precepts of the Emigrant´s Handbook, would allow the construction of a profile of the Spanish migrant as an active element in the daily flow of life, and therefore as an individual and collective expression of Hispanism in America.